2011
DOI: 10.1071/mf10158
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, reproduction and population structure of three gulper sharks (Centrophorus, Centrophoridae) in south-east Australian waters

Abstract: Abstract. Gulper sharks (Centrophorus spp.) are commercially fished in all oceans but the taxonomy and biology of many species are not clearly defined, and stocks are extremely vulnerable to over-exploitation. We present distributional, size-frequency and reproductive data for three species (Centrophorus harrissoni, C. moluccensis and C. zeehaani) that fishing has largely extirpated from the south-east Australian upper continental slope. Trawl-survey catches in 1976-77 from lightly exploited stocks comprised m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 27 publications
4
32
0
3
Order By: Relevance
“…Ebert et al 1992, Cortés 1999, Bulman et al 2002 and stable isotopes (Davenport & Bax 2002, Domi et al 2005 (Pethybridge et al 2011). In contrast, higher TP values were observed in squaliform species, which are well within the range of those previously reported (3.9 to 4.5; Cortés 1999, Bulman et al 2002 and reflect a diet of mainly higher-order fish and squid (Graham & Daley 2011, Pethybridge et al 2011. Using stomach content data and analysed by BrayCurtis dissimilarity indices, Bulman et al (2002) explored the trophic guild structure of the mid-slope and seamount community off southern Tasmania (overlapping with our study area).…”
Section: Assemblage Trophic Structuresupporting
confidence: 43%
“…Ebert et al 1992, Cortés 1999, Bulman et al 2002 and stable isotopes (Davenport & Bax 2002, Domi et al 2005 (Pethybridge et al 2011). In contrast, higher TP values were observed in squaliform species, which are well within the range of those previously reported (3.9 to 4.5; Cortés 1999, Bulman et al 2002 and reflect a diet of mainly higher-order fish and squid (Graham & Daley 2011, Pethybridge et al 2011. Using stomach content data and analysed by BrayCurtis dissimilarity indices, Bulman et al (2002) explored the trophic guild structure of the mid-slope and seamount community off southern Tasmania (overlapping with our study area).…”
Section: Assemblage Trophic Structuresupporting
confidence: 43%
“…Combined (cumulative, across-sector) effort on the upper slope ($ 200-700 m depths) increased from virtually nothing in the early 1970s to near-complete spatial coverage by the mid-2000s; for example, demersal trawling alone covered some 70% of the upper slope in 2005 (Smith et al, 2011). One system-level effect of demersal fishing has been a decline in abundance and distribution of vulnerable species, including groups such as deep-water sharks with low biological productivity (Graham and Daley, 2011;Irvine et al, 2012). Broad-scale depletion of two gulper shark species (C. harrissoni and C. zeehaani) off Southeastern Australia lead to their listing as Conservation Dependent under Australia's EPBC Act in 2013.…”
Section: Implications For Managing and Monitoring Vulnerable Fishery mentioning
confidence: 99%
“…Length and sex data were also collected for many species, particularly for commercial teleosts and sharks, but are not reported here. All specimens of Centrophorus harrissoni, Centrophorus zeehaani and Centrophorus moluccensis were sexed and measured (see Graham and Daley, 2011), and many were tagged with dorsal fin tags and released as part of a broader study investigating movement and home-range.…”
Section: Longline Surveysmentioning
confidence: 99%
“…Estimates of species productivity and intrinsic rebound potential only exist for 2.2% of deep-ocean chondrichthyans (Kyne and Simpfendorfer, 2010), and those that have been assessed have among the lowest values documented for any species of fish to date (Simpfendorfer and Kyne, 2009). In areas where deep-water sharks have been actively targeted by fisheries, dramatic population declines have been triggered (Anderson and Ahmed, 1993;Barbier et al, 2014;Daley et al, 2002;Graham et al, 2001;Graham and Daley, 2011;Jones et al, 2005;Koslow et al, 2000;Morato et al, 2006;White and Kyne, 2010), and it is likely that bycatch of elasmobranchs in deep-water trawl and longline fisheries is having similar negative effects (Graham et al, 2001). Given the slow rate of scientific advancement in the deep-ocean, it has been suggested that many fisheries may become commercially extinct before scientific study can begin (Haedrich et al, 2001).…”
Section: Introductionmentioning
confidence: 96%